Design of a Practical 12 Lead ECG Simulator with a Manikin Demonstrator to Determine Normal or Abnormal Signals Based on Arduino - Kama Yudhistira, Gusti Made Caesar; Kartika, Wisnu; Wardana, Wisnu Kusuma (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Nurses must master several medical tools, including the electrocardiograph (ECG). ECG can detect electrical activity to diagnose heart disorders such as conduction defects, myocardial infarction, and arrhythmias. This tool can record the biomedical potential differences on the surface of the skin generated by the heart by installing recording electrodes at several points on the surface of the body. A manikin doll, with 10 electrodes and 12 tapping points, was utilized as a substitute for the human body. Manikin dolls are replicas of the human body employed in various health fields, serving as a simulation of clinical skills. This study seeks to improve the quality of health services by producing skilled health workers in operating the ECG. The results disclosed that the manikin could produce normal and abnormal signals by implementing a microcontroller-based signal processing system, utilizing the digital-analog converter feature with a resolution of 12 bits. The creation of a resistor divider network circuit, with an input signal from two ESP32 DAC pins, generated 10 output lead channels.